PENGARUH KOMPOSISI PEREKAT TERHADAP KUALITAS BRIKET SEKAM KOPI : The Effect Of Adhesive Composition On The Quality Of Coffee husk Brikets - Eko Wahyudi; Bagus Setyawan; Arfiati Ulfa Utami (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2024)
The ever-increasing need for energy and the dwindling availability of fuel require humans to look for alternative energy sources. Bioarang briquettes are a type of fuel derived from biomass. Biomass is a renewable energy source. One of the biomass used in this research is coffee husks and tapioca as adhesive. This research aims to utilize biomass waste as an slot deposit 5000 alternative fuel and determine the comparison of adhesives using tapioca to produce the best briquettes. In this research, a comparison was made between coffee husks and adhesive with a ratio of 5%, 10%. 15%, 20%, 23%. The tests carried out were water content, ash content, mass density and combustion rate. Based on the results of coffee husks using a variety of adhesives, namely tapioca can be used to produce briquettes. Optimal briquette characteristics were obtained in a 5% sample with a water content value of 3.66%, and a burning rate of 0.231 g/minute with a burning time of 124 minutes.